1976
DOI: 10.1111/j.1600-0765.1976.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the dento‐epithelial junction

Abstract: The detito-epithelial janctions (DEJ) of Rhesus monkeys were examined by electron microscopy. Various fixation procedures were employed in this study. It was revealed that the basal lamina between the junctionai epithelium and the tooth surfaces was composed of three layers: the lamina lucida, the lamina densa and the sub-lamina lucida. Fine filaments often coursed through the lamina densa,, lamina lucida and hemidesmosomes and combined them into a stroctural unit. An electron-dense linear border, presumably d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…muZatta) appeared to be in direct contact with the enamel surface without the presence of any intervening layers such as the dental cuticle and afibrillar cementum. Strands on the enamel side of the lamina densa are likely to be cords, A narrow dense line reported to be present at the surface of the enamel and referred to as the "linear border" (Kobayashi et al, 1976) was not observed in this study. Instead, the surface of the lamina densa was observed to be directly facing the enamel space.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…muZatta) appeared to be in direct contact with the enamel surface without the presence of any intervening layers such as the dental cuticle and afibrillar cementum. Strands on the enamel side of the lamina densa are likely to be cords, A narrow dense line reported to be present at the surface of the enamel and referred to as the "linear border" (Kobayashi et al, 1976) was not observed in this study. Instead, the surface of the lamina densa was observed to be directly facing the enamel space.…”
Section: Discussionmentioning
confidence: 66%
“…In juvenile dogs, the presence of a wide laminated layer of a cuticle was observed. In rhesus monkeys, the internal basement membrane was either in direct contact with the enamel surface or through additional intervening layers such as the cuticle and afibrillar cementum (Kobayashi et al, 1976). Although the lamina lucida of the internal basement membrane was often reported to be difficult to recognize, these investigators reported this basement membrane as being composed of a narrow lamina lucida (14 nm in thickness), lamina densa (40 nm), and a clear layer referred to as the "sublamina lucida" (9.5 nm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these structures, we have also demonstrated that part of the lamina densa, referred to as ''supplementary lamina densa'', was preferentially mineralized and helped maintain firm adhesion between the junctional epithelium and enamel surface in monkey tooth [2]. The dental cuticle is another structure often observed at the dento-gingival interface in healthy human teeth [3][4][5][6][7], periodontitisaffected teeth [8,9], non-human primate teeth [6,10,11], and other animal species [6,12]. Our own work using highresolution electron microscopy has shown that, healthy monkey tooth had a fine network structure similar to that seen in the lamina densa of the internal basal lamina [11].…”
Section: Introductionmentioning
confidence: 97%
“…It directly faced the enamel, and an intervening laminated or non-laminated layer of cuticles was found to be present in dog (Matsson et al, 1979), pig (Marks et al, 1994), monkey (Kobayashi et al, 1976;Sawada & Inoue, 2001b) and man (Listgarten, 1966;Schroeder & Listgarten, 1977). The internal basement membrane was either directly facing the surface of the enamel or doing so through intervening layers of cuticles (Kobayashi et al, 1976;Sawada & Inoue, 2001b) or afibrillar cementum in rhesus monkey (Kobayashi et al, 1976). The latter authors also reported that numerous fine strands crossed the lamina densa of the internal basement membrane at the hemidesmosomes.…”
Section: Attachment Apparatus In Normal Toothmentioning
confidence: 99%